(untitled) (SAARC Journal of Agriculture, 2017)
The allelic diversity and relationship among 120 Aus rice landraces were determined through DNA fingerprinting using microsatellite (SSR) markers. A total of 85 SSR markers were used to characterize and discriminate all tested Aus rice genotypes, 45 of which were polymorphic for different chromosome numbers. The number of alleles per locus varied from 6 alleles (RM484 and RM541) to 30 alleles (RM519) with an average of 13 alleles per locus. The polymorphic information content (PIC) values varied ranged from 0.5211 (RM536) to 0.9369 (RM519) with an average 0.8217. The highest PIC value (0.9369) was obtained for RM519 followed by RM286 (0.9357). The genetic distance-based results seen in the unrooted neighbor-joining tree clustering revealed nine genetic groups. Being grouped into distant clusters and with highest genetic distance, eleven genotypes viz., Atithi dhan, Kadar chap, Pankiraj, Japanese-7, Jamri saity, Logi jota, Joba, Lada moni, Manik Mondal-2, Boilum and Brmulka-2 could be selected as potential parents for crop improvement for their distinctive characters. Panchash and Parija had closest distance in the SSR based CS-Chord distance (0.000) might have same genetic background. The highest genetic dissimilarity (1.000) was found among the nineteen Aus genotypes combinations followed by the second highest (0.9778) among 94 Aus rice combinations. Whereas lowest genetic dissimilarity was found between Kala and Kalo Hizli (0.1778) followed by Holat and Holae (0.2667). This information will be useful in the selection of diverse parents, background selection during backcross breeding programs and assist in broadening germplasm-based rice breeding programs in the near future. SAARC J. Agri., 15(1): 123-137 (2017)